Determining of validity and reliability of achievement goal questionnaire in the veterans and the disables athlete of Khorasan-e Razavi Province - R. Iraji noghondar; H. Poursoltani Zarandi; F. Hadavi (Afarand Scholarly Publishing Institute, 2014)
Background & Purpose: Veterans are a special group of people because of their disabilities, the sports arena has always been faced with restrictions and have difficulties in achieving your goals. Aim: The aim of this study is to determine the validity and reliability of achievement goal questionnaire. Methods & Materials: The statistical population of this study was the veterans and the disables athlete of Khorasan-e Razavi province (N=700) of which 210 samples were selected randomly as the sample. Measurement Instrument was a questionnaire of 12 questions of achievement goal (Sean et al, 2008) included 2 subscales (mastery and ego). The pointing method of questions was based on Likert range five options (wrong completely=1 to True completely=5). Face and content validity of questionnaire was accepted after translation by professors sport management specialists. In order to analyze the data, Cronbach`s alpha for determining reliability, Confirmatory factor analysis to determine the validity and T one-sample test in order to examine differences of the averages the software SPSS and EQS was used. Results: Analytical results showed (α=0.82) reliability for achievement goal questionnaire. All questions had a significant relationship with their agent in reliability of Structure, the amount of relationship and T-value, and they could be a good predictor for their agent. X2/df=2.75, RMSEA=0.068 indexes and RMR=0.001, CFI=0.96, GFI=0.99 confirmed the goodness of models. Also, the results about the relations of factors with the meaning of achievement goal showed that all factors could be a good predictor for the concept of achievement goal. Conclusions: Finally internal and external validity of achievement goal model was accepted and in-country researchers can use this tool to measure the goals of disability Can use in different sports.